2021
DOI: 10.1071/rd20260
|View full text |Cite
|
Sign up to set email alerts
|

Maternal undernutrition during pregnancy and lactation increases transcription factors, ETV5 and GDNF, and alters regulation of apoptosis and heat shock proteins in the testis of adult offspring in the rat

Abstract: We tested whether changes in Sertoli cell transcription factors and germ cell heat shock proteins (HSPs) are linked to the effects of maternal undernutrition on male offspring fertility. Rats were fed ad libitum with a standard diet (CONTROL) throughout pregnancy and lactation or with 50% of CONTROL intake throughout pregnancy (UNP) or lactation (UNL) or both periods (UNPL). After postnatal Day 21, 10 male pups per group were fed a standard diet ad libitum until postnatal Day 160 when testes were processed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 61 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…It is of interest to compare the outcomes of the present study with those from our recent work on the effects of maternal undernutrition during pregnancy or lactation. Notably, undernutrition evoked an opposite effect by increasing IGF-I production, whereas both dietary treatments evoked a decrease in GDNF (Pedrana et al 2020(Pedrana et al , 2021.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It is of interest to compare the outcomes of the present study with those from our recent work on the effects of maternal undernutrition during pregnancy or lactation. Notably, undernutrition evoked an opposite effect by increasing IGF-I production, whereas both dietary treatments evoked a decrease in GDNF (Pedrana et al 2020(Pedrana et al , 2021.…”
Section: Discussionmentioning
confidence: 96%
“…This apparent contradiction can be explained by the well-established post-transcriptional modification of Bcl-2 protein (Greenbaum et al 2003;Ramazi and Zahiri 2021). Indeed, we had previously shown that immunoexpression of Bcl-2 protein caspase-3 increase in parallel (Pedrana et al 2021), consistent with Bcl-2 preventing apoptosis by blocking the release of cytochrome C from the mitochondria. In turn, pores induced by Bax permit the release of mitochondrial cytochrome C into the cytosol, subsequently activating the caspase cascade that leads to apoptosis (Singh et al 2019).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The proliferation of Sertoli cells is an obvious target for DOHAD because Sertoli cell number is fixed at puberty, and adult fertility is largely determined by the ratio of Sertoli cells to germ cells. Indeed, as shown by studies in rats, maternal undernutrition changes the balance between cell proliferation and apoptosis in the developing testes, an essential aspect of the regulation of spermatogenesis (Pedrana et al, 2021).…”
Section: G) Embryo Mortalitymentioning
confidence: 99%
“…4 It appears that maternal undernutrition during pregnancy and lactation impairs the balance between germ cell proliferation and cell death in rats, and this equilibrium is critical for spermatogenesis. 10 Maternal low protein diet also delays the time of puberty in rats and leads to reduced sperm count. [11][12][13] These findings clearly demonstrated the negative impact of maternal undernutrition on male reproduction.…”
Section: Undernutrition and Human Reproduction Prenatal/maternal Unde...mentioning
confidence: 99%